Competitive Ability and Physiological Aspects of Single and Intercropped Arugula (Eruca sativa Miller) - Viana, Caris dos Santos; Guimarães, Marcelo de Almeida; Neto, Hozano de Souza Lemos; Sampaio, ítalo Marlone Gomes; Hendges, Ana Régia Alves de Araújo; Rabelo, Janiquelle da Silva (Journal of Agricultural Studies, 2021)
The aim of this study was to evaluate the competitive ability and physiological aspects of arugula intercropped with different aromatic condiment species. The study was carried out at the Teaching Garden of the Federal University of Ceará, Brazil. A randomised complete block design was used, with four replications and seven treatments: T1 (single arugula), T2 (arugula intercropped with coriander), T3 (arugula and parsley), T4 (arugula and garlic chives), T5 (single coriander), T6 (parsley) and T7 (garlic chives). A physiological evaluation was made of the arugula only. Competitive ability was obtained by calculating the aggressivity index, simplified aggressivity, competitive ratio and compensation ratio. The leaf area index and specific leaf area were calculated. No difference was seen between the treatments with arugula for the physiological factors net photosynthesis, stomatal conductance, rate of transpiration and instant carboxylation efficiency under evaluation within each crop cycle, but there was a difference between the two cycles. The coriander showed the highest aggressivity index and competitive ratio, and was considered more competitive than the arugula, with a higher compensation ratio. As an intercrop, the arugula showed greater competitive ability than the parsley and garlic chives. The greatest leaf area and leaf area index in the arugula plants were seen when intercropped with coriander.